Isolation and production of organic solvent tolerant protease from bacterial burn infection, Staphylococcus aureus KP091274 - Liao, Xin; Teng, Liqun; Li, Wei (Cellular and Molecular Biology, 2021)
Organic solvent-resistant proteases are used to synthesize valuable pharmaceutical and industrial compounds. Using an available and inexpensive source can be very effective in producing this enzyme. For this purpose, Staphylococcus aureus KP091274 was isolated from burn infection and a medium optimization procedure in the presence of organic solvents was considered for four factors of incubation time, the concentration of Mg2+, glycerol and sorbitol using the response surface methodology. The results of this statistical method showed that incubation time has the most effect and glycerol concentration has the least positive effect on enzyme secretion. As a result of applying the optimized conditions in the bacterial culture medium (3mM of Mg2+, 1.5% W/V of glycerol, 0.4% W/V of sorbitol and 72 hours of incubation), the enzyme secretion reaches its maximum.